Efficient integer optimization algorithms for optimal coordination of capacitors and regulators - Baldick, R.; Wu, F.F. (IEEE transactions on power systems, 1990)
The optimal coordination of switched capacitors and tap-changing transformers in a radial distribution system is considered. The formulation incorporates voltage constraints. The coordination problem is approximated by a constrained discrete quadratic optimization using the results from the corresponding unconstrained continuous problem. The discrepancy between the actual and approximating problem is discussed. Two algorithms are proposed to seek solutions to the approximating optimization problem. The first is a randomized algorithm that runs fast but for which there is no guarantee of optimality. The second is a deterministic algorithm, the run time of which is polynomially bounded in the problem size. For large systems the run times of these algorithms may be significantly less than the run times of explicit search or branch and bound algorithms. Test results on a 70 node system confirm the theoretical predictions.< >